At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure, let's solve the expression step-by-step.
We're given the following mathematical expression:
[tex]\[ 1 - 53 + (-19) - 42 - (-22) - (+23) + (+32) + 24 - (-15) \][/tex]
1. Let's start by resolving any subtraction of negative numbers, which translates to addition:
[tex]\[ 1 - 53 + (-19) - 42 + 22 - 23 + 32 + 24 + 15 \][/tex]
2. Next, let's group all the positive numbers and negative numbers separately for clarity:
- Positive numbers: [tex]\( 1 + 22 + 32 + 24 + 15 \)[/tex]
- Negative numbers: [tex]\( -53 + (-19) - 42 - 23 \)[/tex]
3. Now, sum up the positive numbers:
[tex]\[ 1 + 22 + 32 + 24 + 15 \][/tex]
[tex]\[ = 1 + 22 = 23 \][/tex]
[tex]\[ = 23 + 32 = 55 \][/tex]
[tex]\[ = 55 + 24 = 79 \][/tex]
[tex]\[ = 79 + 15 = 94 \][/tex]
4. Sum up the negative numbers:
[tex]\[ -53 + (-19) - 42 - 23 \][/tex]
[tex]\[ = -53 - 19 = -72 \][/tex]
[tex]\[ = -72 - 42 = -114 \][/tex]
[tex]\[ = -114 - 23 = -137 \][/tex]
5. Finally, combine the sums of the positive and negative numbers:
[tex]\[ 94 - 137 = -43 \][/tex]
Thus, the result of the expression [tex]\( 1 - 53 + (-19) - 42 - (-22) - (+23) + (+32) + 24 - (-15) \)[/tex] is
[tex]\[ -43 \][/tex]
We're given the following mathematical expression:
[tex]\[ 1 - 53 + (-19) - 42 - (-22) - (+23) + (+32) + 24 - (-15) \][/tex]
1. Let's start by resolving any subtraction of negative numbers, which translates to addition:
[tex]\[ 1 - 53 + (-19) - 42 + 22 - 23 + 32 + 24 + 15 \][/tex]
2. Next, let's group all the positive numbers and negative numbers separately for clarity:
- Positive numbers: [tex]\( 1 + 22 + 32 + 24 + 15 \)[/tex]
- Negative numbers: [tex]\( -53 + (-19) - 42 - 23 \)[/tex]
3. Now, sum up the positive numbers:
[tex]\[ 1 + 22 + 32 + 24 + 15 \][/tex]
[tex]\[ = 1 + 22 = 23 \][/tex]
[tex]\[ = 23 + 32 = 55 \][/tex]
[tex]\[ = 55 + 24 = 79 \][/tex]
[tex]\[ = 79 + 15 = 94 \][/tex]
4. Sum up the negative numbers:
[tex]\[ -53 + (-19) - 42 - 23 \][/tex]
[tex]\[ = -53 - 19 = -72 \][/tex]
[tex]\[ = -72 - 42 = -114 \][/tex]
[tex]\[ = -114 - 23 = -137 \][/tex]
5. Finally, combine the sums of the positive and negative numbers:
[tex]\[ 94 - 137 = -43 \][/tex]
Thus, the result of the expression [tex]\( 1 - 53 + (-19) - 42 - (-22) - (+23) + (+32) + 24 - (-15) \)[/tex] is
[tex]\[ -43 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.